If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24 + 2 = m + -6 Combine like terms: -24 + 2 = -22 -22 = m + -6 Reorder the terms: -22 = -6 + m Solving -22 = -6 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. -22 + -1m = -6 + m + -1m Combine like terms: m + -1m = 0 -22 + -1m = -6 + 0 -22 + -1m = -6 Add '22' to each side of the equation. -22 + 22 + -1m = -6 + 22 Combine like terms: -22 + 22 = 0 0 + -1m = -6 + 22 -1m = -6 + 22 Combine like terms: -6 + 22 = 16 -1m = 16 Divide each side by '-1'. m = -16 Simplifying m = -16
| 6h-10=15h-80 | | 14=2+2s | | 3x-11=x+21 | | 4+4b=34.4 | | 24=6+7x-5x | | 14x(5-6)= | | 2(y+1)=y-4 | | 2+6s=26 | | 9y-13y=-10-14 | | 19-12a=79 | | x^4-x^2-14x+54=0 | | 93.3=13b-10.7 | | 3x+5+4x=5 | | 4a-1=-37 | | g(0)=3x^2-2x | | 3+4x-18= | | 2-5x=3x-14 | | -5(x-4)=0 | | -216+125x^3=0 | | x+x+1+x+2=90 | | 5(r-5)=2(r-4)-4 | | 3a-19=-49 | | 2(x-3)=34 | | 4x-23=3x-5 | | 6x+9-5x=12 | | 42a^4+60a^3=0 | | 5z+7=6(z-2)-4(2z-3) | | -39=6+5t | | 25x+5(x+5)+10(x-9)=3,115 | | 3(x)=18 | | (5x^4)(25x^2)= | | x+(x+2)+(x+4)=-17 |